Employment and empowerment of rural poor women in Mymensingh District of Bangladesh - Chowdhury, TT; Kowsari, MS; Begum, JA; Khan, MS; Haque, S; Wahid, T (Progressive Agriculture, 2016)
The study was undertaken to identify the factors influencing women empowerment, calculate empowerment index considering the trend of employment. In doing so, the study utilized the data collected by the field survey from Mymensingh districts of Bangladesh. A total number of 60 women respondents were selected using random sampling technique and were categorized into two groups, employed and non-employed, each group comprised equal number of respondents, i.e., 30 women. Data were analyzed using simple statistical techniques as well as OLS regression analysis. An analysis of the socioeconomic status of the women showed that average monthly income difference between employed and non-employed women was BDT 3916 such high difference in average monthly income enabled 70% of the employed women to be empowered whereas with negligible earnings, only 33% of the non-employed women were empowered. The result of the OLS method suggests that the number of children, age gap between husband and wife and income gap between husband and wife significantly affect women empowerment. The five domains of empowerment index indicated that in case of employed group the highest disempowered women (69.44%) in case of leadership domain followed by Production (35.56%), resource (32.41%), income (32.41%) and time domain (23.15%) and in case of non-employed group the highest disempowered women (35.19%) in case of resource domain followed by production (34.57%), leadership (32.10%), income (30.86%) and time domain (4.94%). Results showed that the employed women are more empowered than non-employed women. Therefore, this study strongly suggests that women should be given all the facilities to get involved with income generating activities. Progressive Agriculture 27 (3): 301-310, 2016